ENTIRE CURVE WITH LINEAR DEPENDENT COMPONENTS AND BEFOREHAND SET GREAT NUMBER OF IMPERFECT VECTORS - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
For the beforehand set great number of vectors the whole curve of random continues positive order with linearly dependent components, for which the great number of nevanlinn imperfect vectors coincides with the set great number, is built.